Programmed cell death-related gene IL20RA facilitates tumor progression and remodels tumor microenvironment in thyroid cancer - Yuqi Wang; Yunlong Zhang; Min Liu; Yu Liu; Yu Zeng; Wei Zhang; Shuping Wu; Linfei Hu; Xianhui Ruan; Xiangqian Zheng; Ming Gao; Jingzhu Zhao (Scientific Reports)
Abstract Programmed cell death (PCD) is a vital biological process that is essential for regulating cell progression and tumor microenvironment. This study aimed to explore the relationship between PCD-related genes expression and prognosis in thyroid cancer (THCA), especially IL20RA, as a potential prognostic marker for THCA. Data from The Cancer Genome Atlas (TCGA) database was utilized to develop a PCD-related risk prediction model based on LASSO regression along with univariate Cox regression. The correlation between PCD-related genes and immune cell infiltration was also assessed. The prognostic value of the key PCD-related gene for THCA was investigated by immunohistochemistry. The immune regulatory function and biological function of the key PCD related molecules were detected by cellular experiments. We identified four PCD-related genes (NPC2, E2F1, IL20RA, and TREM2) and constructed a risk model that exhibited excellent accuracy in predicting the prognosis of THCA. Moreover, we confirmed that high expression of IL20RA related to the poor prognosis of THCA. IL20RA promoted cell proliferation and IL20RA knockdown increased apoptosis and ferroptosis. Analysis of the immune microenvironment and detection of macrophages polarization showed that IL20RA promoted the polarization of M2 macrophages while reducing the polarization of M1. We constructed a prognostic prediction model and identified several PCD-related genes. The function of IL20RA which could potentially provide a foundation for additional investigations into diagnostic markers and treatment targets for THCA.